Impact of PBP4 Alterations on β-Lactam Resistance and Ceftobiprole Non-Susceptibility Among Enterococcus faecalis Clinical Isolates - Lazzaro, Lorenzo M.; Cassisi, Marta; Stefani, Stefania; Campanile, Floriana (Frontiers in Cellular and Infection Microbiology, 2022)
Penicillin-resistance among Enterococcus faecalis clinical isolates has been recently associated with overexpression or aminoacidic substitutions in low-affinity PBP4. Ceftobiprole (BPR), a new-generation cephalosporin, is a therapeutic option against E. faecalis. Here, we present evidence that pbp4 gene sequence alterations may influence the expression level of the gene and ceftobiprole binding to PBP4 in E. faecalis clinical isolates showing remarkable MDR-phenotypes, and how this could interfere with BPR in vitro antibacterial and bactericidal activity. Seven E. faecalis strains from bloodstream infections were analyzed for their antibiotic and β-lactam resistance. BPR bactericidal activity was assessed by time-kill analysis; pbp4 genes were sequenced and pbp4 relative expression levels of transcription were performed by RT-qPCR. Five penicillin-resistant ampicillin-susceptible (PRAS) isolates were detected, 4 of which were also BPR non-susceptible (BPR-NS). In the time-kill experiments, BPR exposure resulted in a potent bactericidal activity (3-5 log10 reduction) at the different concentrations tested. pbp4 gene sequence analysis revealed some mutations that may account for the changes in PBP4 affinity and MIC increase in the 4 BPR-NS strains (MICs 4-16 mg/L): the deletion of an adenine (delA) in the promoter region in all PRAS/BPR-NS strains; 12 different amino acid substitutions, 7 of which were next to the PBP catalytic-sites. The most significant were: T418A, located 6 amino acids (aa) upstream of the catalytic-serine included in the 424STFK427motif I; L475Q, 7 aa upstream of the 482SDN484motif II; V606A and the novel Y605H, 13/14 aa upstream of the 619KTGT622motif III. Taken together, our data showed that elevated BPR MICs were attributable to increased transcription of pbp4 - associated with a single upstream adenine deletion and PBP4 alterations in the catalytic-site motifs – which might interfere with the formation of the BPR/PBP4 complex. pbp4 molecular alterations may account for the changes in PBP4 affinity and MIC increase, without affecting BPR cidal activity. Indeed, our in vitro dynamic analysis by time-kill assays showed that BPR exerted a bactericidal activity against E. faecalis clinical isolates, despite their MDR phenotypes.